Al Saj’u fī Asy’āri al Imāmi al Syāfi’ī fī Mauḍu’i Ṭalabi al ‘Ilmi (Dirāsatun Taḥlīliyyatun fī ‘Ilmi al Balāghati) - Nurbaiti, Nurbaiti; Sudiarti, Sri (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2022)
This research discusses about rhyme in Imam Syafi’i poetry with the theme of Studying the purpose of this research is to describe and find out: 1. Any stanzas contained rhyme in Imam Syafi’i poetry about studying. 2. What the types are contained rhyme in Imam Syafi’i poetry about studying. 3. what the most rhyme in Imam Syafi’i poetry about studying and why. The method used in this research is leteratur researchwhich is descriptive qualitative.It can be concluded from the results of this study: 1. There are 48 stanzas that contain rhyme in Imam Syafi’i poetry’s with the theme of Studying. 2. There are 13 mutharraf rhymes and 11 mutawazi rhyme. 3. Mutharraf Rhyme are the most in the reasons as follows: 1. The poet wants to adjust between one stanzas and another so that it can provide beauty in the form of a beatiful tone for the reader to hear. 2. To give a beautiful impression from various aspects in this case, namely in terms of pronunciation. 3. To avoid repitition and avoid saturation of the reader, 4. To clarify the composition and sxpressions so that hey are more beautiful and the poet’s inten is easily conveyed. 5. To make it more memorable to the reader’s heart, this is obtained by the poet from studying the structure of the Qur’an and Hadith